Dasatinib self-assembled nanoparticles decorated with hyaluronic acid for targeted treatment of tumors to overcome multidrug resistance. (1st January 2021) - Zhang, Yawen; Zeng, Xiangle; Wang, Hairong; Fan, Ranran; Hu, Yike; Hu, Xuejie; Li, Jianchun
Abstract: Multidrug resistance (MDR) and lack of targeting specificity are the main reasons why traditional drug therapies fail and produce toxic side effects in cancer chemotherapy. In order to increase targeting specificity and maximize therapeutic efficacy, new intelligent drug delivery systems are needed. In this study, we prepared the hyaluronic acid (HA) conjugated dasatinib (DAS) and D-α-tocopherol acid polyethylene glycolsuccinate (TPGS) copolymer nanoparticles (THD-NPs). The water solubility of the hydrophobic drug DAS was improved by chemically linking with HA. HA can bind to the over-expressed CD44 protein of tumor cells to increase targeting specificity, TPGS can inhibit the activity of P-glycoprotein (P-gp), and increase the intracellular accumulation of drugs. The prepared drug-loaded nanoparticle has a particle size of 82.23 ± 1.07 nm with good in vitro stability. Our in vitro studies showed that THD-NPs can be released more rapidly in a weakly acidic environment (pH = 5.5) than in a normal physiological environment (pH = 7.4), which can realize the selective release of nanoparticles in tumor cells. Compared to free drugs, THD-NPs showed more efficient cellular uptake, effectively increased the cytotoxic effect of DAS on nasopharyngeal carcinoma HNE1 cells drug resistance HNE1/DDP cells and increased the accumulation of drugs in HNE1/DDP cells, which may be due to the inhibitory effect of TPGS on the efflux function of P-gp. In vivo experiments showed that THD-NPs can effectively inhibit tumor growth without obvious side effects. In conclusion, the targeted and pH-sensitive nanosystem, we designed has great potential to overcome drug resistance and increase therapeutic effects in cancer treatment.